A Rho scaffold integrates the secretory system with feedback mechanisms in regulation of auxin distribution - Hazak, Ora; Bloch, Daria; Poraty, Limor; Sternberg, Hasana; Zhang, Jing; Jirí Friml; Yalovsky, Shaul (PLoS Biology)
Development in multicellular organisms depends on the ability of individual cells to coordinate their behavior by means of small signaling molecules to form correctly patterned tissues. In plants, a unique mechanism of directional transport of the signaling molecule auxin between cells connects cell polarity and tissue patterning and thus is required for many aspects of plant development. Direction of auxin flow is determined by polar subcellular localization of PIN auxin efflux transporters. Dynamic PIN polar localization results from the constitutive endocytic cycling to and from the plasma membrane, but it is not well understood how this mechanism connects to regulators of cell polarity. The Rho family small GTPases ROPs/RACs are master regulators of cell polarity, however their role in regulating polar protein trafficking and polar auxin transport has not been established. Here, by analysis of mutants and transgenic plants, we show that the ROP interactor and polarity regulator scaffold protein ICR1 is required for recruitment of PIN proteins to the polar domains at the plasma membrane. icr1 mutant embryos and plants display an a array of severe developmental aberrations that are caused by compromised differential auxin distribution. ICR1 functions at the plasma membrane where it is required for exocytosis but does not recycle together with PINs. ICR1 expression is quickly induced by auxin but is suppressed at the positions of stable auxin maxima in the hypophysis and later in the embryonic and mature root meristems. Our results imply that ICR1 is part of an auxin regulated positive feedback loop realized by a unique integration of auxin-dependent transcriptional regulation into ROP-mediated modulation of cell polarity. Thus, ICR1 forms an auxin-modulated link between cell polarity, exocytosis, and auxin transport-dependent tissue patterning.

Subcellular trafficking of PIN auxin efflux carriers in auxin transport - Jirí Friml (European Journal of Cell Biology)
The directional transport of the plant hormone auxin is a unique process mediating a wide variety of developmental processes. Auxin movement between cells depends on AUX1/LAX, PGP and PIN protein families that mediate auxin transport across the plasma membrane. The directionality of auxin flow within tissues is largely determined by polar, subcellular localization of PIN auxin efflux carriers. PIN proteins undergo rapid subcellular dynamics that is important for the process of auxin transport and its directionality. Furthermore, various environmental and endogenous signals can modulate trafficking and polarity of PIN proteins and by this mechanism change auxin distribution. Thus, the subcellular dynamics of auxin transport proteins represents an important interface between cellular processes and development of the whole plant. This review summarizes our recent contributions to the field of PIN trafficking and auxin transport regulation. © 2009 Elsevier GmbH.

PIN phosphorylation is sufficient to mediate PIN polarity and direct auxin transport - Zhang, Jing; Nodzyński, Thomasz; Pěnčík, Aleš; Rolčík, Jakub; Jirí Friml (PNAS)
The plant hormone auxin plays a crucial role in regulating plant development and plant architecture. The directional auxin distribution within tissues depends on PIN transporters that are polarly localized on the plasmamembrane. The PINpolarity and the resulting auxin flow directionality aremediated by the antagonistic actions of PINOID kinase and protein phosphatase 2A. However, the contributionof the PINphosphorylationto the polar PINsortingis still unclear. Here, we identified an evolutionarily conserved phosphorylation site within the central hydrophilic loop of PIN proteins that is important for the apical and basal polar PIN localizations. Inactivation of the phosphorylation site in PIN1(Ala) resulted in a predominantly basal targeting and increased the auxinflowto the root tip. In contrast, the outcome of the phosphomimic PIN1(Asp) manipulation was a constitutive, PINOID-independent apical targeting of PIN1 and an increased auxin flow in the opposite direction. Furthermore, the PIN1(Asp) functionally replaced PIN2 in its endogenous expression domain, revealing that the phosphorylation-dependent polarity regulation contributes to functional diversification within the PIN family. Our data suggest that PINOID-independent PIN phosphorylation at one single site is adequate to change the PIN polarity and, consequently, to redirect auxin fluxes between cells and provide the conceptual possibility and means to manipulate auxin-dependent plant development and architecture.

Role of PIN-mediated auxin efflux in apical hook development of Arabidopsis thaliana - Žádníková, Petra; Petrášek, Jan; Peter Marhavy; Raz, Vered; Vandenbussche, Filip; Ding, Zhaojun; Schwarzerová, Kateřina; Morita, Miyo T; Tasaka, Masao; Hejátko, Jan; Van Der Straeten, Dominique; Jirí Friml; et al. (Development)
The apical hook of dark-grown Arabidopsis seedlings is a simple structure that develops soon after germination to protect the meristem tissues during emergence through the soil and that opens upon exposure to light. Differential growth at the apical hook proceeds in three sequential steps that are regulated by multiple hormones, principally auxin and ethylene. We show that the progress of the apical hook through these developmental phases depends on the dynamic, asymmetric distribution of auxin, which is regulated by auxin efflux carriers of the PIN family. Several PIN proteins exhibited specific, partially overlapping spatial and temporal expression patterns, and their subcellular localization suggested auxin fluxes during hook development. Genetic manipulation of individual PIN activities interfered with different stages of hook development, implying that specific combinations of PIN genes are required for progress of the apical hook through the developmental phases. Furthermore, ethylene might modulate apical hook development by prolonging the formation phase and strongly suppressing the maintenance phase. This ethylene effect is in part mediated by regulation of PIN-dependent auxin efflux and auxin signaling.

Trafficking to the outer polar domain defines the root soil interface - Łangowski, Łukasz; Růžička, Kamil; Naramoto, Satoshi; Kleine-Vehn, Jürgen; Jirí Friml (Current Biology)
In animals, the interface between organism and environment is constituted by the epithelium [1]. In plants, the exchange of nutrients and signals between root and soil is crucial for their survival, but the cellular mechanisms underlying the epithelium-like function and specific localization of proteins to the root surface have not been identified [2]. Here we analyze the mechanism of polar delivery to the root-soil interface of the proteins BOR4, ABCG37, and PEN3, which transport nutrients [2], transport plant hormones, and are required for pathogen defense [3], respectively. The simultaneous visualization of these proteins and the apical and basal cargos in a single cell demonstrates that the outermost cell side represents an additional polar domain. Delivery to this outer polar domain depends on ARF GEF [4] and actin [5-8] function but does not require known molecular components of the apical or basal targeting. The outer polar delivery is, in contrast to known basal and apical cargos [9, 10], mediated by the polar secretion. Our findings show that the outermost cell membranes of roots define an additional polar domain in plant cells along with a specific, previously uncharacterized, polar targeting mechanism that is important for defining the functional, epithelium-like root-soil interface.

Probing plant membranes with FM dyes: Tracking dragging or blocking? - Jelínková, Adriana; Malínská, Kateřina; Sibu Simon; Kleine-Vehn, Jürgen; Pařezová, Markéta; Pejchar, Přemysl; Kubeš, Martin; Martinec, Jan; Jirí Friml; Zažímalová, Eva; Petrášek, Jan (Plant Journal)
Remarkable progress in various techniques of in vivo fluorescence microscopy has brought an urgent need for reliable markers for tracking cellular structures and processes. The goal of this manuscript is to describe unexplored effects of the FM (Fei Mao) styryl dyes, which are widely used probes that label processes of endocytosis and vesicle trafficking in eukaryotic cells. Although there are few reports on the effect of styryl dyes on membrane fluidity and the activity of mammalian receptors, FM dyes have been considered as reliable tools for tracking of plant endocytosis. Using plasma membrane-localized transporters for the plant hormone auxin in tobacco BY-2 and Arabidopsis thaliana cell suspensions, we show that routinely used concentrations of FM 4-64 and FM 5-95 trigger transient re-localization of these proteins, and FM 1-43 affects their activity. The active process of re-localization is blocked neither by inhibitors of endocytosis nor by cytoskeletal drugs. It does not occur in A. thaliana roots and depends on the degree of hydrophobicity (lipophilicity) of a particular FM dye. Our results emphasize the need for circumspection during in vivo studies of membrane proteins performed using simultaneous labelling with FM dyes.

Arabidopsis PIS1 encodes the ABCG37 transporter of auxinic compounds including the auxin precursor indole 3 butyric acid - Růžička, Kamil; Strader, Lucia C; Bailly, Aurélien; Yang, Haibing; Blakeslee, Joshua; Łangowski, Łukasz; Nejedlá, Eliška; Fujita, Hironori; Itoh, Hironori; Syōno, Kunihiko; Hejátko, Jan; Gray, William M; et al. (PNAS)
Differential distribution of the plant hormone auxin within tissues mediates a variety of developmental processes. Cellular auxin levels are determined by metabolic processes including synthesis, degradation, and (de)conjugation, as well as by auxin transport across the plasma membrane. Whereas transport of free auxins such as naturally occurring indole-3-acetic acid (IAA) is well characterized, little is known about the transport of auxin precursors and metabolites. Here, we identify amutation in the ABCG37 gene of Arabidopsis that causes the polar auxin transport inhibitor sensitive1 (pis1) phenotype manifested by hypersensitivity to auxinic compounds. ABCG37 encodes the pleiotropic drug resistance transporter that transports a range of synthetic auxinic compounds as well as the endogenous auxin precursor indole-3-butyric acid (IBA), but not free IAA. ABCG37 and its homolog ABCG36 act redundantly at outermost root plasma membranes and,unlike established IAA transporters from the PIN and ABCB families, transport IBA out of the cells. Our findings explore possible novel modes of regulating auxin homeostasis and plant development by means of directional transport of the auxin precursor IBA and presumably also other auxin metabolites.

Auxin regulates distal stem cell differentiation in Arabidopsis roots - Ding, Zhaojun; Jirí Friml (PNAS)
The stem cell niche in the root meristem is critical for the development of the plant root system. The plant hormone auxin acts as a versatile trigger in many developmental processes, including the regulation of root growth, but its role in the control of the stem cell activity remains largely unclear. Here we show that local auxin levels, determined by biosynthesis and intercellular transport, mediate maintenance or differentiation of distal stem cells in the Arabidopsis thaliana roots. Genetic analysis shows that auxin acts upstream of the major regulators of the stem cell activity, the homeodomain transcription factor WOX5, and the AP-2 transcription factor PLETHORA. Auxin signaling for differentiation of distal stem cells requires the transcriptional repressor IAA17/AXR3 as well as the ARF10 and ARF16 auxin response factors. ARF10 and ARF16 activities repress the WOX5 transcription and restrict it to the quiescent center, where WOX5, in turn, is needed for the activity of PLETHORA. Our investigations reveal that long-distance auxin signals act upstream of the short-range network of transcriptional factors to mediate the differentiation of distal stem cells in roots.

The GATA factor HANABA TARANU is required to position the proembryo boundary in the early Arabidopsis embryo - Nawy, Tal; Bayer, Martin; Mravec, Jozef; Jirí Friml; Birnbaum, Kenneth D; Lukowitz, Wolfgang (Developmental Cell)
Division of the Arabidopsis zygote defines two fundamentally different developmental domains, the proembryo and suspensor. The resulting boundary separates domain-specific gene expression, and a signal originating from the proembryo instructs the suspensor to generate the root stem cell niche. While root induction is known to require the phytohormone auxin and the Auxin Response Factor MONOPTEROS, it has remained largely elusive how the two domains involved in this process are initially specified. Here, we show that the GATA factor HANABA TARANU (HAN) is required to position the inductive proembryo boundary. Mutations in HAN cause a coordinated apical shift of gene expression patterns, revealing that HAN regulates transcription in the basal proembryo. Key auxin transporters are affected as early as the 8 cell stage, resulting in apical redistribution of auxin. Remarkably, han embryos eventually organize a root independent of MONOPTEROS and the suspensor around a new boundary marked by the auxin maximum.

The AP 3 β adaptin mediates the biogenesis and function of lytic vacuoles in Arabidopsis - Feraru, Elena; Paciorek, Tomasz; Feraru, Mugurel I; Zwiewka, Marta; De Groodt, Ruth; De Rycke, Riet M; Kleine-Vehn, Jürgen; Jirí Friml (Plant Cell)
Plant vacuoles are essential multifunctional organelles largely distinct from similar organelles in other eukaryotes. Embryo protein storage vacuoles and the lytic vacuoles that perform a general degradation function are the best characterized, but little is known about the biogenesis and transition between these vacuolar types. Here, we designed a fluorescent marker- based forward genetic screen in Arabidopsis thaliana and identified a protein affected trafficking2 (pat2) mutant, whose lytic vacuoles display altered morphology and accumulation of proteins. Unlike other mutants affecting the vacuole, pat2 is specifically defective in the biogenesis, identity, and function of lytic vacuoles but shows normal sorting of proteins to storage vacuoles. PAT2 encodes a putative β-subunit of adaptor protein complex 3 (AP-3) that can partially complement the corresponding yeast mutant. Manipulations of the putative AP-3 β adaptin functions suggest a plant-specific role for the evolutionarily conserved AP-3 β in mediating lytic vacuole performance and transition of storage into the lytic vacuoles independently of the main prevacuolar compartment-based trafficking route.

The march of the PINs: Developmental plasticity by dynamic polar targeting in plant cells - Grunewald, Wim; Friml, Jirí (EMBO Journal)
Development of plants and their adaptive capacity towards ever‐changing environmental conditions largely depend on the spatial distribution of the plant hormone auxin. At the cellular level, various internal and external signals are translated into specific changes in the polar, subcellular localization of auxin transporters from the PIN family thereby directing and redirecting the intercellular fluxes of auxin. The current model of polar targeting of PIN proteins towards different plasma membrane domains encompasses apolar secretion of newly synthesized PINs followed by endocytosis and recycling back to the plasma membrane in a polarized manner. In this review, we follow the subcellular march of the PINs and highlight the cellular and molecular mechanisms behind polar foraging and subcellular trafficking pathways. Also, the entry points for different signals and regulations including by auxin itself will be discussed within the context of morphological and developmental consequences of polar targeting and subcellular trafficking.

Plasma membrane-bound AGC3 kinases phosphorylate PIN auxin carriers at TPRXS(N/S) motifs to direct apical PIN recycling - Dhonukshe, Pankaj; Huang, Fang; Galván Ampudia, Carlos; Mähönen, Ari; Kleine Vehn, Jürgen; Xu, Jian; Quint, Ab; Prasad, Kalika; Friml, Jiřĺ; Scheres, Ben; Offringa, Remko (Development)
Polar membrane cargo delivery is crucial for establishing cell polarity and for directional transport processes. In plants, polar trafficking mediates the dynamic asymmetric distribution of PIN FORMED (PIN) carriers, which drive polar cell-to-cell transport of the hormone auxin, thereby generating auxin maxima and minima that control development. The Arabidopsis PINOID (PID) protein kinase instructs apical PIN localization by phosphorylating PINs. Here, we identified the PID homologs WAG1 and WAG2 as new PIN polarity regulators. We show that the AGC3 kinases PID, WAG1 and WAG2, and not other plant AGC kinases, instruct recruitment of PINs into the apical recycling pathway by phosphorylating the middle serine in three conserved TPRXS(N/S) motifs within the PIN central hydrophilic loop. Our results put forward a model by which apolarly localized PID, WAG1 and WAG2 phosphorylate PINs at the plasma membrane after default non-polar PIN secretion, and trigger endocytosis-dependent apical PIN recycling. This phosphorylation-triggered apical PIN recycling competes with ARF-GEF GNOM-dependent basal recycling to promote apical PIN localization. In planta, expression domains of PID, WAG1 and WAG2 correlate with apical localization of PINs in those cell types, indicating the importance of these kinases for apical PIN localization. Our data show that by directing polar PIN localization and PIN-mediated polar auxin transport, the three AGC3 kinases redundantly regulate cotyledon development, root meristem size and gravitropic response, indicating their involvement in both programmed and adaptive plant development.

Arabidopsis ROOT UVB SENSITIVE2 WEAK AUXIN RESPONSE1 is required for polar auxin transport - Ge, Lei; Peer, Wendy A; Robert, Stéphanie; Swarup, Ranjan; Ye, Songqing; Prigge, Michael J; Cohen, Jerry D; Jirí Friml; Murphy, Angus S; Tang, Ding; Estelle, Mark A (Plant Cell)
Auxin is an essential phytohormone that regulates many aspects of plant development. To identify new genes that function in auxin signaling, we performed a genetic screen for Arabidopsis thaliana mutants with an alteration in the expression of the auxin-responsive reporter DR5rev:GFP (for green fluorescent protein). One of the mutants recovered in this screen, called weak auxin response1 (wxr1), has a defect in auxin response and exhibits a variety of auxin-related growth defects in the root. Polar auxin transport is reduced in wxr1 seedlings, resulting in auxin accumulation in the hypocotyl and cotyledons and a reduction in auxin levels in the root apex. In addition, the levels of the PIN auxin transport proteins are reduced in the wxr1 root. We also show that WXR1 is ROOT UV-B SENSITIVE2 (RUS2), a member of the broadly conserved DUF647 domain protein family found in diverse eukaryotic organisms. Our data indicate that RUS2/WXR1 is required for auxin transport and to maintain the normal levels of PIN proteins in the root.

ABP1 mediates auxin inhibition of clathrin-dependent endocytosis in Arabidopsis - Robert, Stéphanie; Kleine-Vehn, Jürgen; Barbez, Elke; Sauer, Michael; Paciorek, Tomasz; Pawel Baster; Vanneste, Steffen; Zhang, Jing; Sibu Simon; Čovanová, Milada; Hayashi, Kenichiro; Dhonukshe, Pankaj; et al. (Cell)
Spatial distribution of the plant hormone auxin regulates multiple aspects of plant development. These self-regulating auxin gradients are established by the action of PIN auxin transporters, whose activity is regulated by their constitutive cycling between the plasma membrane and endosomes. Here, we show that auxin signaling by the auxin receptor AUXIN-BINDING PROTEIN 1 (ABP1) inhibits the clathrin-mediated internalization of PIN proteins. ABP1 acts as a positive factor in clathrin recruitment to the plasma membrane, thereby promoting endocytosis. Auxin binding to ABP1 interferes with this action and leads to the inhibition of clathrin-mediated endocytosis. Our study demonstrates that ABP1 mediates a nontranscriptional auxin signaling that regulates the evolutionarily conserved process of clathrin-mediated endocytosis and suggests that this signaling may be essential for the developmentally important feedback of auxin on its own transport.

Cell surface- and Rho GTPase-based auxin signaling controls cellular interdigitation in Arabidopsis - Xu, Tongda; Wen, Mingzhang; Nagawa, Shingo; Fu, Ying; Chen, Jin-Gui; Wu, Ming-Jing; Perrot-Rechenmann, Catherine; Jirí Friml; Jones, Alan M; Yang, Zhenbiao (Cell)
Auxin is a multifunctional hormone essential for plant development and pattern formation. A nuclear auxin-signaling system controlling auxin-induced gene expression is well established, but cytoplasmic auxin signaling, as in its coordination of cell polarization, is unexplored. We found a cytoplasmic auxin-signaling mechanism that modulates the interdigitated growth of Arabidopsis leaf epidermal pavement cells (PCs), which develop interdigitated lobes and indentations to form a puzzle-piece shape in a two-dimensional plane. PC interdigitation is compromised in leaves deficient in either auxin biosynthesis or its export mediated by PINFORMED 1 localized at the lobe tip. Auxin coordinately activates two Rho GTPases, ROP2 and ROP6, which promote the formation of complementary lobes and indentations, respectively. Activation of these ROPs by auxin occurs within 30 s and depends on AUXIN-BINDING PROTEIN 1. These findings reveal Rho GTPase-based auxin-signaling mechanisms, which modulate the spatial coordination of cell expansion across a field of cells.

Endoplasmic reticulum: The rising compartment in auxin biology - Friml, Jirí; Jones, Angharad (Plant Physiology)

Immunolocalization of proteins in plants - Sauer, Michael; Jirí Friml (Plant Developmental Biology)
Rapid advances in the field of plant biology, especially in plant cell biology, have created the need for methods that allow the localization of proteins in situ at subcellular resolution. Although in many cases recombinant proteins with fluorescent proteins can fulfill this task, antibody-based immunological detection of proteins is a complementary technique, which avoids the risk of inducing side effects by a fusion protein, such as misexpression, mistargeting, altered stability, or toxicity. Moreover, recombinant protein techniques are applicable only to a rather limited set of model plants. The immunolocalization protocols presented here can be used to display protein localization patterns in different tissues of various plant species. This chapter describes a whole mount immunolocalization protocol, which has been extensively used in Arabidopsis roots and some above-ground tissues, and that also works in other species. Additionally, for bulky or hard tissue types, a variation of this protocol for paraffin-embedded sections is given.

Emergence of tissue polarization from synergy of intracellular and extracellular auxin signaling - Krzysztof Wabnik; Kleine-Vehn, Jürgen; Balla, Jozef; Sauer, Michael; Naramoto, Satoshi; Reinöhl, Vilém; Merks, Roeland M; Govaerts, Willy J; Jirí Friml (Molecular Systems Biology)
Plant development is exceptionally flexible as manifested by its potential for organogenesis and regeneration, which are processes involving rearrangements of tissue polarities. Fundamental questions concern how individual cells can polarize in a coordinated manner to integrate into the multicellular context. In canalization models, the signaling molecule auxin acts as a polarizing cue, and feedback on the intercellular auxin flow is key for synchronized polarity rearrangements. We provide a novel mechanistic framework for canalization, based on up-to-date experimental data and minimal, biologically plausible assumptions. Our model combines the intracellular auxin signaling for expression of PINFORMED (PIN) auxin transporters and the theoretical postulation of extracellular auxin signaling for modulation of PIN subcellular dynamics. Computer simulations faithfully and robustly recapitulated the experimentally observed patterns of tissue polarity and asymmetric auxin distribution during formation and regeneration of vascular systems and during the competitive regulation of shoot branching by apical dominance. Additionally, our model generated new predictions that could be experimentally validated, highlighting a mechanistically conceivable explanation for the PIN polarization and canalization of the auxin flow in plants.

Gravity induced PIN transcytosis for polarization of auxin fluxes in gravity sensing root cells - Kleine-Vehn, Jürgen; Ding, Zhaojun; Jones, Angharad R; Tasaka, Masao; Morita, Miyo T; Jirí Friml (PNAS)
Auxin is an essential plant-specific regulator of patterning processes that also controls directional growth of roots and shoots. In response to gravity stimulation, the PIN3 auxin transporter polarizes to the bottomside of gravity-sensing root cells, presumably redirecting the auxin flux toward the lower side of the root and triggering gravitropic bending. By combining live-cell imaging techniques with pharmacological and genetic approaches, we demonstrate that PIN3 polarization does not require secretion of de novo synthesized proteins or protein degradation, but instead involves rapid, transient stimulation of PIN endocytosis, presumably via a clathrin-dependent pathway. Moreover, gravity-induced PIN3 polarization requires the activity of the guanine nucleotide exchange factors for ARF GTPases (ARF-GEF) GNOM-dependent polar-targeting path-ways and might involve endosome-based PIN3 translocation from one cell side to another. Our data suggest that gravity perception acts at several instances of PIN3 trafficking, ultimately leading to the polarization of PIN3, which presumably aligns auxin fluxes with gravity vector and mediates downstream root gravitropic response.

ADP ribosylation factor machinery mediates endocytosis in plant cells - Naramoto, Satoshi; Kleine-Vehn, Jürgen; Robert, Stéphanie; Fujimoto, Masaru; Dainobu, Tomoko; Paciorek, Tomasz; Ueda, Takashi; Nakano, Akihiko; Van Montagu, Marc C; Fukuda, Hiroo; Jirí Friml (PNAS)
Endocytosis is crucial for various cellular functions and development of multicellular organisms. In mammals and yeast, ADP-ribosylation factor (ARF) GTPases, key components of vesicle formation, and their regulators ARF-guanine nucleotide exchange factors (GEFs) and ARF-GTPase-activating protein (GAPs) mediate endocytosis. A similar role has not been established in plants,mainly because of the lack of the canonical ARF and ARF-GEF components that are involved in endocytosis in other eukaryotes. In this study, we revealed a regulatory mechanism of endocytosis in plants based on ARF GTPase activity.Weidentified that ARF-GEFGNOMand ARF-GAP VASCULAR NETWORK DEFECTIVE 3 (VAN3), both of which are involved in polar auxin transport-dependent morphogenesis, localize at the plasma membranes as well as in intracellular structures. Variable angle epifluorescence microscopy revealed that GNOM and VAN3 localize to partially overlapping discrete foci at the plasmamembranes that are regularly associated with the endocytic vesicle coat clathrin. Genetic studies revealed that GNOM and VAN3 activities are required for endocytosis and internalization of plasma membrane proteins, including PIN-FORMED auxin transporters. These findings identified ARF GTPase-based regulatory mechanisms for endocytosis in plants. GNOMand VAN3 previously were proposed to function solely at the recycling endosomes and trans-Golgi networks, respectively. Therefore our findings uncovered an additional cellular function of these prominent developmental regulators.